Catalytic Synthesis of 1, 2, 4, 5‐Tetrasubstituted 1H‐Imidazole Derivatives: State of the Art. Issue 12 (29th March 2019) - Rossi, Renzo; Angelici, Gaetano; Casotti, Gianluca; Manzini, Chiara; Lessi, Marco
Abstract: Tetrasubstituted 1 H ‐imidazoles are a large family of heteroarene derivatives that are known to include natural products isolated from marine sponges and synthetic compounds possessing a broad range of biological and pharmacological properties. Consequently, a great deal of attention has been given to the synthesis of these heteroarenes and reviews covering some synthetic aspects of this topic have been published in recent years. However, none of these reviews provides a comprehensive overview of the catalytic methods developed in the literature for the preparation of this important class of heteroarenes. This article aims to provide an updated critical picture of the catalytic processes reported in the literature up to the end of 2017 for the synthesis of 1, 2, 4, 5‐tetrasubstituted 1 H ‐imidazoles illustrating these protocols and their characteristic features such as scope, efficiency, versatility, and limitations. The review also summarizes the mechanisms proposed for many of the reported processes. Abstract :